Beyond condorcet: Optimal aggregation rules using voting records - Eyal Baharad; Jacob Goldberger; Moshe Koppel; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2011)
The difficulty of optimal decision making in uncertain dichotomous choice settings is that it requires information on the expertise of the decision makers (voters). This paper presents a method of optimally weighting voters even without testing them against questions with known right answers. The method is based on the realization that if we can see how voters vote on a variety of questions, it is possible to gauge their respective degrees of expertise by comparing their votes in a suitable fashion, even without knowing the right answers.
Keywords: D70; 330; Abstimmungsparadoxon; Public Choice; Theorie